Formation of Mn doped CH3NH3PbBr3 perovskite microrods and their collective EMP lasing. (20th December 2017) - Zou, Shuangyang; Gong, Zhihong; Liang, Bianbian; Hou, Lipeng; Liu, Ruibin; Zhong, Haizheng; Zou, Bingsuo; Kavokin, A V
Abstract: Diluted magnetic semiconductor (DMS) nanostructures are promising platform to modulate carriers and spins for new information devices. Here we report that the high quality pure CH3 NH3 PbBr3 microrods and Mn doped CH3 NH3 PbBr3 microrods have been prepared by solution method and in which the exciton magnetic polarons (EMP) formed in Mn doped microrods, and a single mode lasing phenomenon from collective EMP in single microrod have been detected when excited by fs pulse laser. This finding helps to understand the exciton and spin interactions and pave ways to the realization of new type of bosonic laser.